Cost-effectiveness of active surveillance versus early surgery for thyroid micropapillary carcinoma based on diagnostic and treatment norms in China - Lai, Min; Zhang, Miao Miao; Qin, Qing Qing; An, Yu; Li, Yan Ting; Yuan, Wen Zhen (Frontiers in Endocrinology, 2023)
In this study, we compared the cost-effectiveness comparison of the active surveillance (AS) and early surgery (ES) approaches for papillary thyroid microcarcinoma (PTMC) from the perspective of the Chinese healthcare system.We performed a cost-effectiveness analysis using a Markov model of PTMC we developed to evaluate the incremental cost-effectiveness ratio of AS and ES. Our reference case was of a 40-year-old female diagnosed with unifocal (<10 mm) PTMC. Relevant data were extracted after an extensive literature review, and the cost incurred in each state was determined using China Medicare data on payments for ES and AS. The willingness-to-pay threshold was set at ¥242928/ quality-adjusted life-year (QALY) gained. Sensitivity analyses were performed to account for any uncertainty in the model's variables. Additional subgroup analyses were performed to determine whether AS was cost-effective when different initial monitoring ages were used.Results: ES exhibited an effectiveness of 5.2 QALYs, whereas AS showed an effectiveness of 25.8 QALYs. Furthermore, the incremental cost-effectiveness ratio for ES versus AS was ¥1009/QALY. The findings of all sensitivity analyses were robust. Compared with ES, AS was found to be the cost-effective strategy at initial monitoring ages of 20 and 60 years, with an incremental cost-effectiveness ratio of ¥3431/QALY and -¥1316/ QALY at 20 and 60 years, respectively. AS was a more cost-effective strategy in patients with PTMC aged more than 60.With respect to the norms of the Chinese healthcare system, AS was more cost-